Pembuatan Website Usaha Susu Kedelai Sehat Jaya - Husni Lubis; Akbar Fachrezi; Ainil Arbie; Fahri Effendy; Ihsan Lubis (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The new normal era has made many changes to human life patterns. Resulting in changing marketing patterns. Previously marketing was via person to person, banners, pamphlets or the like. In this new era, people's habits are changing by using the internet more for the activities they need. For this reason, it is necessary to change the marketing pattern by utilizing the internet as a marketing medium. Website is one way to introduce the product of a business. Become wider. Jaya healthy soy milk business is one of the MSME businesses whose marketing is still conventional. The service team is trying to help increase marketing by creating a website for marketing business products. The results of this activity are expected that MSMEs can market their business products more broadly.